Visual Neglect and Mental Representations: Current Status and Issues - Brase, Emma (Kansas State University. K-State Libraries, 2017)
Visual neglect is a cognitive condition that results from right posterior parietal hemisphere brain damage due to stroke, which usually causes perception deficits on the left side of space. Neglect related symptoms can range widely in diversity and intensity, making it difficult to establish consistent ways of treating and addressing individual behaviors of neglect. An interesting subcategory of neglect is representational neglect. This type of neglect affects an individual’s mental representation of space. Lack of perception on the left side of space can also extend to mental imagery used when performing tasks dealing with numbers, time, spatial awareness, and memory. This review paper covers literature that discusses the cause of visual neglect and assessment of its neuropsychological effects, as well as the specific disorders of input it causes. Research in neuroscience, and specifically the topic of visual neglect, gained traction in the late 1970s and early 1980s. Early research remains relevant, since it describes the basic physical symptoms that can be observed in neglect patients, and the general region of the brain that is affected. However, with increasingly advancing technology, more current research can explore the condition much further and more accurately. Additionally, further research on representational neglect has expanded the kinds of assessments used to diagnose and understand the condition. There are still unknown characteristics of neglect, including how different reference frames of neglect alter both visual and mental perception, if past personal memories are affected after developing neglect, and the relationship between severity of neglect and difficulty in processing the passage of time. All of these topics are in need of further research.
Citation: Brase, E. (2017). Visual Neglect and Mental Representations: Current Status and Issues. Unpublished manuscript, Kansas State University, Manhattan, KS.
Kirmser Undergraduate Research Award - Individual Freshman category, grand prize
Keywords: Visual neglect; Brain damage; Stroke; Representational neglect; Head injury assessment